2017
DOI: 10.25103/ijbesar.101.03
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement Factor for Organizational Excellence

Abstract: The objective of this publication is to identify ways to increase employee engagement in Bulgarian business organizations and identify how such employee engagement affects employee and company performance. Design/methodology/approach: Our research is based on the evaluation of employee engagement methodologies used by well-known companies such as Gallup HCM Advisory Group, Deloitte and Aon Hewitt. Based on these, we derive the factors influencing employee engagement in Bulgarian companies. Findings: This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…The engaged employees internalize the goals and strategies of the organization, contribute effectively and perceive organizational success as their own success (Stoyanova & Iliev, 2017). Engaged employees are passionate about entertaining their customers.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The engaged employees internalize the goals and strategies of the organization, contribute effectively and perceive organizational success as their own success (Stoyanova & Iliev, 2017). Engaged employees are passionate about entertaining their customers.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Organizations with low employee engagement suffer from 65% lower share price over time, 37% lower job growth, 16% lower profitability, and 18% lower productivity (Seppälä & Cameron, 2015). On the other hand, companies with disengaged employees suffer from the waste of effort, earn less commitment from the workers, face raised absenteeism, and have less customer orientation, less labor productivity, and reduced operating and net profit margins (Stoyanova & Iliev, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They mentioned the study conducted by Harter et al (2002), saying employee engagement is a "soft index" that impacts the efficiency of organizations. Stoyanova and Iliev (2017) used the methodology adopted by Gallup HCM Advisory Group, Deloitte, and Aon Hewitt to study employee engagement and derive the factors influencing employee engagement in Bulgarian companies. Stoyanova and Iliev (2017) concluded that engaged employees are willing to contribute and know precisely how to work effectively because they clearly understand their employer's goals and strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stoyanova and Iliev (2017) used the methodology adopted by Gallup HCM Advisory Group, Deloitte, and Aon Hewitt to study employee engagement and derive the factors influencing employee engagement in Bulgarian companies. Stoyanova and Iliev (2017) concluded that engaged employees are willing to contribute and know precisely how to work effectively because they clearly understand their employer's goals and strategy. Organizations with engaged employees have a higher level of employee retention due to reduced turnover and intention to leave the company, performance, gainfulness, customer satisfaction, and growth.…”
Section: Literature Reviewmentioning
confidence: 99%